2017
DOI: 10.1530/jme-17-0014
|View full text |Cite
|
Sign up to set email alerts
|

Berberine reduced blood pressure and improved vasodilation in diabetic rats

Abstract: Hyperglycemia and hypertension are considered to be the two leading risk factors for vascular disease in diabetic patients. However, few pharmacologic agents could provide a combinational therapy for controlling hyperglycemia and hypertension at the same time in diabetes. The objectives of this study are to investigate whether berberine treatment could directly reduce blood pressure and identify the molecular mechanism underlying the vascular protection of berberine in diabetic rats. Berberine was intragastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…The concentration of berberine in the extract was similar to the concentration of berberine used as pure standard as reported in other studies (e. g. 75 mg,100mg, 120mg, 200mg) [19][20][21][22].…”
Section: The Effect Of Bve On Renal Functionsupporting
confidence: 81%
“…The concentration of berberine in the extract was similar to the concentration of berberine used as pure standard as reported in other studies (e. g. 75 mg,100mg, 120mg, 200mg) [19][20][21][22].…”
Section: The Effect Of Bve On Renal Functionsupporting
confidence: 81%
“…Furthermore, pro-and antiinflammatory mediators released from perivascular adipose tissue are involved in the development of atherosclerosis [181], suggesting that adipocytes may play a key role in diabetes-associated cardiovascular dysfunctions. The results demonstrated that berberine could protect cardiovascular functions by reducing the risk of hypertension [123,126] and coagulation [134], attenuating cardiac hypertrophy [115,129,132] and cardiac arrhythmias [110,113], and inhibiting potential cardiovascular damages associated with dyslipidemia [74,114,116,[119][120][121]124,125,130,135,136]. In addition, berberine reduced obesity and cardiovascular risk at least in part via modulating adipocyte populations and inflammatory state in the adipose tissues [112,117,118,128,131].…”
Section: Vascular Protectionmentioning
confidence: 96%
“…Berberine has also been shown to reduce total cholesterol and LDL-C in clinical trials [23,60]. In studies in vitro, berberine alleviated palmitate-induced endothelial dysfunction via upregulation of endothelial nitric oxide synthase (eNOS) and downregulation of nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) [114], an enzyme involved in age-associated cardiovascular dysfunction via oxidative stress and inflammation [150]; it also inhibited HG-potentiated platelet aggregation [134], suppressed HGinduced endothelial dysfunction and restored NO generation possibly via suppressing ectopic miR-133a expression and restoring peroxisome proliferator-activated receptor (PPAR) γ and AMPK signaling [44,121,123,125,126]. In another study, it reduced oxidized LDL-induced inflammatory responses in macrophages via AMPK activation and nuclear factor (NF)-B inhibition [135].…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…It is present in several medicinal plants, such as Berberis vulgaris, Coptis chinensis, Hydrastis canadensis, Coptidis rhizoma, Xanthoriza simplicissima, Phellodendron amurense, and Chelidonium majus. Berberine exhibits unusual biochemical and pharmacological activities, including antidiabetic [1], hypolipidemic [2], antihypertensive [3], anti-inflammatory [4], antidiarrheal [5], hepatoprotective [6], antidepressant [7], anticancer [8], antibacterial [9], and antiviral [10] properties. BBR is capable of penetrating all cell lines, but the cumulative concentration is the highest in Hep G-2 cells [11].…”
Section: Introductionmentioning
confidence: 99%